Maternal bisphenols exposure and thyroid function in children: a systematic review and meta-analysis - Liu, Jiani; Tian, Min; Qin, Haiyue; Chen, Danrong; Mzava, Sabitina Mrisho; Wang, Xu; Bigambo, Francis Manyori (Frontiers in Endocrinology, 2024)
Background: Evidence from animal experiments and epidemiological studies has reported controversial results about the effects of prenatal bisphenols (BPs) exposure on childhood thyroid function. This study aims to explore the associations of prenatal exposure to BPs with thyroid-related hormones (THs) in newborns and early childhood, with a particular focus on the sex-dependent and exposure level effects.Methods: Correlated studies were systematically searched from PubMed, Web of Science, Medline, Cochrane, and Embase until February 21, 2024. The exposures assessed include bisphenol A (BPA), bisphenol F (BPF), bisphenol S (BPS), bisphenol AF (BPAF), and tetrachlorobisphenol A (TCBPA). THs measured were thyroid stimulating hormone (TSH), total tri-iodothyronine (TT3), total thyroxine (TT4), free tri-iothyronine (FT3), and free thyroxine (FT4). Effect estimates were quantified using coefficients from multivariable regression models. Statistical analyses were completed using Stata 16.0. The methodological quality of the included studies was evaluated using the Newcastle-Ottawa Scale (NOS).Results: Eleven cohort studies comprising 5,363 children were included in our meta-analysis. Prenatal bisphenol concentrations were statistically significant related to alterations in thyroid hormones in children, exclusively in female offspring, including reduced TSH (β = -0.020, 95% CI: -0.036, -0.005) and increased TT3 levels (β = 0.011, 95% CI: 0.001, 0.021), and exposure to high concentration of bisphenols (>1.5 ug/g creatinine) significantly reduced FT3 levels in children (β = -0.011, 95% CI: -0.020, -0.003).Prenatal bisphenol exposure is linked to alterations in thyroid hormone levels in girls, necessitating enhanced measures to control bisphenol exposure levels during pregnancy for child health protection.